Extant microbial communities in the partially desiccated Rincon de Parangueo maar crater lake in Mexico. Issue 5 (10th April 2019) - Sánchez-Sánchez, Janet; Cerca, Mariano; Alcántara-Hernández, Rocío J; Lozano-Flores, Carlos; Carreón-Freyre, Dora; Levresse, Gilles; Vega, Marina; Varela-Echavarría, Alfredo; Aranda-Gómez, Jose Jorge
ABSTRACT: Rincon de Parangueo is a maar where a perennial lake was present until the 1980s. A conspicuous feature of the lake's sediments is the presence of bioherms and organo-sedimentary deposits produced by microbial communities. The gradual lake desiccation during the last 40 years has produced dramatic environmental changes inside the maar basin, which resulted in the formation of a highly saline-alkaline system with extant microorganisms. In this paper we succinctly describe the geologic setting where the microbial communities have developed inside of the maar crater and the results obtained from high-throughput sequencing methods to characterize the microbial component (Bacteria, Eukarya and Archaea) in endolithic mats of calcareous sediments, and microbial mats and free-living microorganisms in the soda ponds. The studied sites displayed different microbial communities with a diverse number of phylotypes belonging to Bacteria and Eukarya, contrasting with a much less diverse component in Archaea. The sequences here detected were related to environmental sequences from sites with extreme life conditions such as high alkalinity (alkaliphiles), high salinity (halophiles) and high temperature (thermophiles). Moreover, our results indicate an important unexplored endemic microbial biodiversity in the vestiges of the former lake that need to be studied. Abstract : Extant microbial communities of Rincon de Parangueo maar crater, Mexico